PENGARUH MOTIVASI, PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Pudji Astuty dan Arief Bramantyo (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aims to analyzethe influence of motivation, work experience and work discipline on employee performance. This study took a sample of employees at PT MulyaPrivate Indra55 people by using the calculation method Likert scale. The results of this study showed that the variables of motivation, experience and discipline to have a significant influence on the performance variables. Keywords : Motivation, work experience, work discipline, employee performance